2016
DOI: 10.1002/path.4781
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR‐24‐3p impedes T‐cell function by targeting FGF11 and serves as a potential prognostic biomarker for nasopharyngeal carcinoma

Abstract: Recent studies have shown that extracellular microRNAs are not only potential biomarkers but are also involved in cell interactions to regulate the intercommunication between cancer cells and their microenvironments in various types of malignancies. In this study, we isolated exosomes from nasopharyngeal carcinoma (NPC) cell lines and patient sera (T-EXOs), or control NP69 cells and healthy donor sera (HD-EXOs). We found that miR-24-3p was markedly enriched in T-EXOs as compared with HD-EXOs; the serum exosoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
139
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(151 citation statements)
references
References 43 publications
3
139
0
Order By: Relevance
“…As NPC is highly correlated to the Epstein-Barr virus (EBV) infection, EBV viral RNAs (miRNAs56, long non-coding RNAs7) and proteins are of diagnostic powers. In clinical practice, EBV capsid antigen IgA (VCA-IgA), early antigen Ig A (EA-IgA), nuclear antigen (EBNA1) IgA, and circulating EBV DNA are widely used for diagnosis and screening of NPC8910.…”
mentioning
confidence: 99%
“…As NPC is highly correlated to the Epstein-Barr virus (EBV) infection, EBV viral RNAs (miRNAs56, long non-coding RNAs7) and proteins are of diagnostic powers. In clinical practice, EBV capsid antigen IgA (VCA-IgA), early antigen Ig A (EA-IgA), nuclear antigen (EBNA1) IgA, and circulating EBV DNA are widely used for diagnosis and screening of NPC8910.…”
mentioning
confidence: 99%
“…For example, regulatory T cells (Tregs), a subset of CD4 + T cells recruited by cancer cells to evade the immune system [131], can be recruited via EV-signals sent out by cancer cells. Nasopharyngeal carcinoma cells shed EVs enriched with miR-24-3p, which influences the differentiation of T cells and their ability to engage Treg cells [132,133]. Similarly, Lewis lung carcinoma cells transfer miR-214 in EVs to T cells, downregulating Phosphate and Tensin Homolog protein (PTEN) and promoting Treg expansion [134].…”
Section: Mirnas In Evs Drive Immune Modulation During Metastasis Formmentioning
confidence: 99%
“…As examples of the other major research focus of exosomes, miRNAs in salivary exosomes are considered potential biomarkers of aging (Machida et al, 2015), while exosomes from a tumor microenvironment are prominently associated with cancer cell metabolism (Zhao et al, 2016). Exosomes containing miR-24-3p depress T cell function and may serve as a prognostic marker for nasopharyngeal carcinoma (Ye et al, 2016). In addition, a recent study found that bovine milk-derived exosomes can be used for oral delivery of the chemotherapeutic drug paclitaxel, which elevates drug stability and reduces systemic and immunogenic toxicities compared to administering the drug alone (Agrawal et al, 2017).…”
Section: Current Research Progressmentioning
confidence: 99%